2019
DOI: 10.1186/s13756-019-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of self-medication with antibiotics in Maputo City: a qualitative study

Abstract: BackgroundMozambique classifies but does not yet enforce antibiotics as prescription-only-medicine (POM) allowing the public access to a variety of antibiotics that otherwise are provided on prescription. This contributes to the growing practice of self-medication with antibiotics (SMA) which systematically exposes individuals to the risk of developing antibiotic resistance, antibiotic side effects and increases the health service costs and morbidity. This study aimed at describing the patterns of SMA among Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 16 publications
6
55
1
2
Order By: Relevance
“…Despite the fact that antibiotics in Mozambique may be presented in different pharmaceutical forms or capsules of colours which may confuse the users, one important finding was the ability of some participants to define antibiotics, influenced by their familiarisation with Amoxicillin, which locally is typically presented in the form of yellow and red tipped capsules. This finding is concordant to the recent research conducted by Torres (2019) in Mozambique, which reported that participants reported to know Amoxicillin, describing the capsules with in red and yellow colour [ 30 ]. Apart from limiting their conceptualisation to an attempt to characterise Amoxicillin, they were not able to conceptually distinguish antibiotics from other types of medicines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the fact that antibiotics in Mozambique may be presented in different pharmaceutical forms or capsules of colours which may confuse the users, one important finding was the ability of some participants to define antibiotics, influenced by their familiarisation with Amoxicillin, which locally is typically presented in the form of yellow and red tipped capsules. This finding is concordant to the recent research conducted by Torres (2019) in Mozambique, which reported that participants reported to know Amoxicillin, describing the capsules with in red and yellow colour [ 30 ]. Apart from limiting their conceptualisation to an attempt to characterise Amoxicillin, they were not able to conceptually distinguish antibiotics from other types of medicines.…”
Section: Discussionsupporting
confidence: 91%
“…The first official situation analysis on antibiotic use and resistance in Mozambique suggests that there are likely high levels of inappropriate antibiotic use at the community level and it recommends the rationalisation of antibiotic use in the community as one of the strategies to reduce antibiotic resistance [ 29 ]. Two recent studies conducted in Mozambique confirmed both the existence of inappropriate use of antibiotics at the community level and the prevalence of self-medication via the purchase of non-prescribed antibiotics [ 28 , 30 ]. Additionally, both studies conducted in urban areas revealed the limited knowledge of antibiotic use that the study population held.…”
Section: Introductionmentioning
confidence: 99%
“…The improper use of antibiotics through self‐medication is associated with substantial adverse reactions, such as antibiotic resistance, toxicity and treatment insufficiency 14,16 . Self‐medication with antibiotics can be divided into: (i) direct self‐medication which includes patients purchasing antibiotics without a prescription, reusing old prescriptions and leftover antibiotics and (ii) indirect self‐medication which refers to purchasing antibiotics after seeking the advice of a pharmacist or accepting the antibiotics recommended by friends and family members 4,17 …”
Section: Introductionmentioning
confidence: 99%
“…18 Evidence has accumulated concerning SMA in different sub-Saharan African countries and for different populations. 3,17,19,20 Among those studies addressing antibiotic self-medication, few have covered parents self-medicating their under-fives. Since children are at an increased risk of succumbing to infectious diseases because of their relatively less developed immune systems, 21 they are more prone to SMA.…”
Section: Introductionmentioning
confidence: 99%